Problems of Multinacional Literature course - Užkalnis, P. (Literatūra, 1975)
The author of the paper reviews the history of the Soviet Union national literature of a 40-year period, its various construction methods and variants, and the projects of "The Program," upholding the historical course construction principle. Synthesizing the USSR national literature process, the author marks off the typological parallels of the multinational literary process, singling out the evolution of the concept of the human being as the most important. The author refers to the tenets of the classics of Marxism that "history is not something indefinite" but is created by the real, live man, pursuing his aim, creating the surroundings in which he himself is moulded.In the solution of methodological and methodical problems of the USSR national literature, its division into periods, and the course construction questions, the principle of integration is used. The author refers to the history of philosophy and aesthetics, the Soviet Union and the world history, the experience of the USSR national literature teaching, and the latest data of the history of multinational literature. F. Engels' idea that one cannot level the self-independence of ideology, politics, literature, and art is underlined in the article. The USSR national literature course should not copy the periods of other branches of science but find out and fix its own periods of literature development, which would reflect quantitative and qualitative changes of the multinational literature process.In the article, the author guided himself by the laws of dialectical materialism—the continuous development of literature and art, the uninterrupted quantitative and qualitative changes leading to the crisis that marks the transformation from one quality to another, the end of one period and the beginning of the other. Consequently, the author divides the 17-century history of the USSR national literature (4th–20th centuries, the Soviet period included) into 6 periods:the formation of belles-lettres (4th–9th centuries),the classical (9th–10th centuries),the transitional period (16th–17th centuries),the formation of Enlightenment ideas (18th century),the period of realism (19th–the beginning of the 20th century),the Soviet period.
Keywords: -